PENGELOLAAN UNSI (SANGGAR BUDAYA) DALAM TRADISI PERTUNJUKAN SENI DENDANG SERAWAI, BENGKULU - Bustanuddin Lubis; Mohamad Yoesoef; Pudentia (UNIB Press, 2023)
The goal to be achieved in the discussion of this article is the management of unsi in the tradition of performing seni dendang Serawai in Bengkulu. The process of maintaining an oral tradition is more related to the performance of the tradition than to the presence of traditional performers. Currently, the tradition of performing seni dendang is performed by a cultural unit formed independently by the community. Unsi, as actors and executors of performances, certainly experience a management process in their organizational management. Based on the results of observations in the fields of Seluma Regency and South Bengkulu Regency, it turns out that most of the unsi do not yet have good and healthy management. The research method used is qualitative, with direct interview data collection techniques and field research. The results of the study found that there were internal and external factors that became obstacles in the development of unsi in performances seni dendang. Internal factors relate to the performance seni dendang itself, while external factors relate to the supporters of the performance seni dendang. Paying attention to the role and function of unsi is one of the important keys to caring for the tradition of seni dendang Serawai .